A distributed lag non-linear time-series study of ambient temperature and healthcare-associated infections in Hefei, China. Issue 3 (4th March 2023) - Wu, Yile; Liang, Mingming; Liang, Qiwei; Yang, Xiyao; Sun, Yehuan
ABSTRACT: Little is known about the effects of temperature on healthcare-associated infections (HAIs). A distributed lag non-linear model was used to estimate the association between ambient temperature and HAIs in Hefei, China. In total, 9, 592 HAIs were included. The effect of low temperature (−0.1°C, 2.5th percentile) was significant on the current day (RR = 1.108, 95%CI:1.003–1.222), and then appeared on the 4th day (RR = 1.045, 95%CI:1.007–1.084) and the 5th day (RR = 1.033, 95%CI:1.006–1.061). The cumulative lag effects of low temperature lasted from the 5th to 10th days (RR = 1.123–1.143), and a long-term cumulative lag effect was observed on the 14th day (RR = 1.157, 95%CI:1.001–1.338). The lag effect of high temperature (31.0°C, 97.5th percentile) was not statistically significant. However, the effects of temperatures on HAIs were not significant among gender or age subgroups. This study suggests that the low temperatures have acute and lag effects on HAIs in Hefei, China.